THE ROLE OF BIOMARKERS IN THE PREDICTION AND EARLY DIAGNOSIS OF ACUTE MYOCARDIAL INFARCTION. - Ribeiro Pereira, Felipe (2024)
Acute myocardial infarction (AMI) is a critical condition that continues to be one of the leading causes of death worldwide, highlighting the need for effective methods for early diagnosis and risk prediction. This study carried out an integrative review of the literature, focusing on evaluating the role of biomarkers such as high-sensitivity troponins (hs-cTn), B-type natriuretic peptide (BNP/NT-proBNP) and microRNAs in the early detection of AMI. The analysis revealed that high-sensitivity troponins are currently the gold standard for identifying myocardial injury, due to their high sensitivity and specificity, allowing diagnosis even in the early stages of infarction. Additional biomarkers such as BNP and microRNAs have proven useful in risk stratification, providing complementary information about hemodynamic status and inflammatory processes. However, challenges such as the interference of chronic conditions, such as renal failure, and the high cost of laboratory tests for microRNAs still limit their routine clinical application. It is concluded that the integration of multiple biomarkers and the development of more comprehensive diagnostic protocols can significantly improve the diagnostic accuracy and personalized treatment of patients with AMI.